Dynamic mass based sound transmission loss prediction of vibro-acoustic metamaterial double panels applied to the mass-air-mass resonance. (3rd March 2019) - de Melo Filho, N.G.R.; Van Belle, L.; Claeys, C.; Deckers, E.; Desmet, W.
Abstract: To enhance the sound insulation performance of double panel partitions at their mass-air-mass resonance frequency, novel compact and low-mass solutions are sought. This paper investigates the use of the locally resonant vibro-acoustic metamaterial concept as a possible solution. The metamaterial solution is applied to one panel of a double panel partition in order to enhance the sound transmission loss at the mass-air-mass resonance. To design the metamaterial solution and predict its sound transmission loss performance, an extension of the multiple reflection theory is proposed, incorporating the dynamic mass of a metamaterial panel. The latter is obtained from the metamaterial plate dispersion curves, calculated using finite element based unit cell modeling. The designed metamaterial solution is manufactured and its insertion loss is measured. The novel design outperforms the original double panel and an equivalent total mass double panel configuration in the targeted mass-air-mass resonance frequency region. The predictions obtained with the proposed method are in good agreement with the experimentally obtained results. This demonstrates the potential of the metamaterial solution to enhance the acoustic insulation at the mass-air-mass resonance and indicates that the proposed method allows a fast, simple and representative indication of their acoustic insulation performance. Highlights: Double panel STL is enhanced at the mass-air-mass frequency using locally resonant metamaterials. A unit cell based dynamic mass calculation based on the dispersion curves is proposed. Fast STL prediction method is proposed using the multiple reflection theory combined with the dynamic mass. A transparent metamaterial double panel partition is designed, manufactured and tested experimentally. Good agreement between proposed method and experimental results.